Compact 8x8 butler matrix for ISM band - Cheung, Lester Ted Kong (2005)
Mitigation of interference due to multiple signals coexisting in the same frequency band can be achieved through the implementation of a smart antenna system that employs scanning of multiple and simultaneously available beams. These multiple and simultaneously available beams can be generated through beamforming networks such as the Butler Matrix, of which its design is the focus of this thesis. By employing passive devices in a butterfly layout configuration, a completely planar microstrip 8x8 Butler Matrix to perform in the ISM Band of 2.4 GHz to 2.5 GHz was designed. Recently, research has been focusing on the miniaturization of passive microwave devices and components. Artificial Transmissions Lines is a relatively new method that achieves miniaturization of a transmission line through periodically loading the line capacitively in order to lower the phase velocity characteristic of a high impedance line to an appropriate value. The higher the impedance of the line in question, the greater the level of miniaturization obtained. 40 percent area savings and 59 percent area savings were achieved in the design of the passive component hybrid and crossover structures, respectively, compared to conventional design methods. Through the implementation of 12 hybrids, 8 fixed phase shifters and 16 crossover structures, the final layout of a compact Butler Matrix can be designed. Simulations were performed using Microwave Office electromagnetic packages. Design calculations were verified using MatchCad.